1996
DOI: 10.1175/1520-0469(1996)053<2813:sspoai>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Single Scattering Properties of Atmospheric Ice Crystals

Abstract: When plane waves diffract through fractal-patterned apertures, the resulting far-field profiles or diffractals also exhibit iterated, self-similar features. Here we show that this specific architecture enables robust signal processing and spatial multiplexing: arbitrary parts of a diffractal contain sufficient information to recreate the entire original sparse signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
434
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(459 citation statements)
references
References 6 publications
12
434
0
2
Order By: Relevance
“…Optical phenomena such as the 22 • halo (and 46 • halo) were first explained by Mariotte (1717) as being due to the refraction of light (in the visible) by randomly oriented hexagonal ice crystals. Modelling studies of scattering phase functions show that these features are an indication of highly regular pristine ice crystals (see among others Takano and Liou, 1989;Iaquinta et al, 1995;Macke et al, 1996a;Yang et al, 2001;Um and McFarquhar, 2010). Observations of cloud ice particles tend to show much smoother scattering behaviour compared with modelling results obtained in laboratory studies (Sassen and Liou, 1979;Crépel et al, 1997;Barkey et al, 2002).…”
Section: Introductionmentioning
confidence: 86%
“…Optical phenomena such as the 22 • halo (and 46 • halo) were first explained by Mariotte (1717) as being due to the refraction of light (in the visible) by randomly oriented hexagonal ice crystals. Modelling studies of scattering phase functions show that these features are an indication of highly regular pristine ice crystals (see among others Takano and Liou, 1989;Iaquinta et al, 1995;Macke et al, 1996a;Yang et al, 2001;Um and McFarquhar, 2010). Observations of cloud ice particles tend to show much smoother scattering behaviour compared with modelling results obtained in laboratory studies (Sassen and Liou, 1979;Crépel et al, 1997;Barkey et al, 2002).…”
Section: Introductionmentioning
confidence: 86%
“…Air bubble inclusion also plays an important role in causing the difference in g between the two models, for it is known that nonabsorbing inclusions, such as air bubbles, reduces forwardscattering and increases the side and back-scattering (Macke et al, 1996a). Both fractal and roughened surfaces can also have effects on the scattering properties of ice particles similar to air bubble inclusion, i.e., smoothing out scattering features and reducing the asymmetry factor (Macke et al, 1996b;Yang et al, 2008).…”
Section: Modis and Polder Ice Optical Thickness Retrieval Algorithmsmentioning
confidence: 99%
“…Since initial work that identified crystal shapes using in situ ob-servations of ice clouds (e.g., Weickmann, 1948, and studies summarized by Dowling and Radke, 1990, and by Heymsfield and McFarquhar, 2002), much effort has been devoted to quantify the microphysical and scattering properties of ice crystals. One important finding is that ambient atmospheric conditions (e.g., temperature and humidity) govern the growth and morphological properties of ice crystals (e.g., aufm Kampe et al, 1951;Lamb and Scott, 1974;Gonda, 1980;Fukuta and Takahashi, 1999;Bacon et al, 2003;Bailey and Hallett, 2002, 2012Korolev et al, 2004) upon which the corresponding scattering properties depend (e.g., Takano and Liou, 1995;Macke et al, 1996;Yang and Liou, 1998;Baran et al, 2001Baran et al, , 2005Yang et al, 2005Yang et al, , 2013Um and McFarquhar, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that the assumed L-W relationship impacts the single-scattering properties of ice crystals (Macke et al, 1996, Um and McFarquhar, 2007Yang and Fu, 2009;van Diedenhoven et al, 2014a), satellite retrievals (Han et al, 1999), and numerical simulations (Fu, 2007;Sheridan et al, 2009;Sulia and Harrington, 2011;Dearden et al, 2012). In addition, new modeling approaches (e.g., Sulia and Harrington, 2011) that explicitly predict particle properties rather than using predefined ice categories as in traditional schemes require statistical databases of L and W .…”
Section: Introductionmentioning
confidence: 99%